Clinical Assessment of Spiritual Psychology: A Case Study of Cancer Co- Patients - Ahmad, Naseem (International Journal of Psychosocial Rehabilitation, 2020)
Spirituality is quite essential for patients who are suffering from cancer-like life-threatening illnesses. The significance of spiritual requirements is pretty essential for terminally ill cancer patients. The most examined category to frame a specific structure with the relation of the assessment and cure of the chronic illness therapy-Spiritual (FACIT-Sp) results in the cancer patients clusters through a demonstrative literature review, methodology, and the analysis of collected data. The literature review shows that the patients suffering from the assessment of the effect show the lowest scores on the Meaning and Faith subscales. It has been also found that the highest scores of Faith have been achieved by the cancer patients who have survived. This study has given several data on FACIT-Sp score for the diagnosis of cancer survivors, patients, and severely ill cancer patients to mention necessary highlights of the meaning of the assessment in detail.